Synergy of photocatalysis and fuel cells: A chronological review on efficient designs, potential materials and emerging applications - John, Sangeeth; Nogala, Wojciech; Gupta, Bhavana; Singh, Shubra (Frontiers in Chemistry, 2022)
The energy demand required to provide clean water for the world population makes energy scarcity and water pollution two sides of the same coin. Renewable energy sources are the only way out in order to provide energy in a sustainable manner for the ever-increasing demands of the modern world. A renewable energy source which can also provide clean water will be of immense interest and that is where Photocatalytic Fuel Cells (PFCs) exactly fit in. PFCs hold the ability to produce electric power with simultaneous photocatalytic degradation of pollutants on exposure to light. Different strategies, including conventional Photoelectrochemical cell design, have been technically upgraded to exploit the advantage of PFCs and to widen their applicability. Parallel to the research on design, researchers have put an immense effort into developing materials/composites for electrodes and their unique properties. The efficient strategies and potential materials have opened up a new horizon of applications for PFCs. Recent research reports reveal this persistently broadening arena which includes hydrogen and hydrogen peroxide generation, carbon dioxide and heavy metal reduction and even sensor applications. The review reported here consolidates all the aspects of various design strategies, materials and applications of PFCs. The review provides an overall understanding of PFC systems, which possess the potential to be a marvellous renewable source of energy with a handful of simultaneous applications. The review is a read to the scientific community and early researchers interested in working on PFC systems.